The real learning environments as a pedagogical strategy for the development of the mathematical competences in secondary school students - Alvis-Puentes, Johnny Fernando; Aldana-Bermúdez, Eliécer; Caicedo-Zambrano, Segundo Javier (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article focuses on the analysis of the students’ performances when they face with the resolution of a learning environment from real research scenarios in order to develop mathematical competences from critical mathematical education. The research project was developed under a qualitative study, with a comprehensive cut, where the population is composed by 9th grade students of a Colombian educational Institution. The learning environment is related to the public service of aqueduct, sewerage and cleanliness in the town of Campoalegre, State of Huila, Colombia, which allows establishing an approximate reflection on the way mathematics operates as a part of society, contributing to the consolidation of a critical and reflective student. From results, it is concluded how the learning environments allow articulating didactically the development of mathematical competences in the classroom, from real situations in the students' context, promoting a critical citizenship in front of the reality described in the learning environments. Then, they reveal how experience and collaborative work are intertwined to assume judgments that are woven from their subjectivities of the society in which they are immersed.